2018
DOI: 10.1063/1.5042229
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of numerical error in pore-scale lattice Boltzmann simulations with simple bounce-back rule: Analysis and highly accurate extrapolation

Abstract: We perform the viscosity-independent Stokes flow simulations in regular sphere packings using the two-relaxation-times (TRT) lattice Boltzmann method (LBM) with the simple bounce-back (BB) rule. Our special discretization procedure reduces the scatter in integral quantities, such as drag force, and quantifies the solution convergence error. We assume transition to linear (−1) convergence rate for different sets of TRT parameters and use this assumption to provide a simple extrapolation scheme. After establishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Previous studies have also observed this convergence with increasing resolution, albeit not always from above (e.g., Zakirov and Galeev, 2019). Similar behavior has also been observed in Lattice-Boltzmann method (LBM) simulations (e.g., Khirevich et al, 2015;Khirevich and Patzek, 2018).…”
Section: Newtonian Flowsupporting
confidence: 76%
See 3 more Smart Citations
“…Previous studies have also observed this convergence with increasing resolution, albeit not always from above (e.g., Zakirov and Galeev, 2019). Similar behavior has also been observed in Lattice-Boltzmann method (LBM) simulations (e.g., Khirevich et al, 2015;Khirevich and Patzek, 2018).…”
Section: Newtonian Flowsupporting
confidence: 76%
“…Furthermore, sandstone is known to be an ideal reservoir rock and is of certain interest for several geological fields, especially in exploration geology. Laboratory measurements of the given sample with porosity ≈ 15.2 % result in a permeability value of ≈ 1100 mD (Keehm, 2003).…”
Section: Application To Fontainebleau Sandstonementioning
confidence: 99%
See 2 more Smart Citations
“…Once converged, we can evaluate the force acting on the sphere and compare it against existing quasi-analytical solutions [48]. Due to its simplicity and the existence of a quasi-analytical solution, it is a well-studied setup, both for classical DNS approaches [49] as well as for the LBM [39,41,27,50]. For LBM simulations, this is a particularly important test as some collision operators suffer from an undesired dependence of the drag force on the relaxation rate s ν , which affects the simulated boundary location [39].…”
Section: Resultsmentioning
confidence: 99%